Rampant [videorecording (DVD)] - Kim, Sung-hoon (director); Hyŏn, Pin, 1982-; Chang, Tong-gŏn, 1972-; Seo, Ji-hye (Well Go USA Entertainment, 2019)
When murderous creatures known as night demons overrun ancient Korea, Prince Ganglim must gather the strength of his entire kingdom to destroy them.